Trends and hotspots in pulmonary rehabilitation research from 2003 to 2024: bibliometric and visualization analysis - LUO Mengxian; LI Xinrui; ZHANG Chi (Yixue xinzhi zazhi)
Objective To analyze the current research status and hotspots in the field of pulmonary rehabilitation (PR) technology.Methods Computer retrieval of PR related literature in the Web of Science core database was conducted from January 2003 to April 2024. VOSviewer 1.6.19 and CiteSpace 6.2.R4 were used to analyze the quantity, authors, countries or regions, institutions, and keywords of PR related literature.Results From 2003 to 2024, 3,913 English literatures related to PR were published, and the overall number of publications in the PR field showed an upward trend. The United States was the country with the highest publication volume, with Spruit MA and Maastricht University being the authors and institutions with the highest number of relevant literature published, respectively. Quality of life, COPD, exercise, rehabilitation, and physical activity were the main research topics, while intervention methods, lung function, and intervention feasibility have received more attention in recent years.Conclusion In recent years, PR research has shown an overall upward trend, with research hotspots and frontiers mainly focused on quality of life, COPD, exercise, physical activity, lung function, intervention methods, feasibility. More relevant research can be conducted on PR intervention methods, lung function, and feasibility to promote the clinical practical application of PR.